2016
DOI: 10.1172/jci87532
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte MyD88 and IRAK4 control inflammatory and fibrotic responses to tissue injury

Abstract: Fibrotic disease is associated with matrix deposition that results in the loss of organ function. Pericytes, the precursors of myofibroblasts, are a source of pathological matrix collagens and may be promising targets for treating fibrogenesis. Here, we have shown that pericytes activate a TLR2/4- and MyD88-dependent proinflammatory program in response to tissue injury. Similarly to classic immune cells, pericytes activate the NLRP3 inflammasome, leading to IL-1β and IL-18 secretion. Released IL-1β signals thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 58 publications
6
97
0
Order By: Relevance
“…Informed permission for the use of fetal tissues was obtained from all patients. The isolation of cells was approved by the University of Washington Institutional Review Board (IRB447773EA) and performed at the University of Washington Medical Center as previously described (81). Details of the materials and methods for this study can be found in SI Appendix, SI Materials & Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Informed permission for the use of fetal tissues was obtained from all patients. The isolation of cells was approved by the University of Washington Institutional Review Board (IRB447773EA) and performed at the University of Washington Medical Center as previously described (81). Details of the materials and methods for this study can be found in SI Appendix, SI Materials & Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, our mining of RNAseq datasets from lung fibroblasts derived from slow and rapid progressing IPF patient lung samples, and normal lung samples supports an expansion of a PDGFRß- and PDGFRα-expressing stromal population in IPF. Further, various studies have suggested that pericytes express higher levels of innate immune microbial sensors[13, 88] and IPF lung fibroblasts, notably from progressive IPF patients, express TLR9[78, 79] and TLR4[77], and the activation of these microbial sensors leads to myofibroblast differentiation[7779]. Together, these studies suggest that pericyte-derived fibroblasts and myofibroblasts are present in IPF, and these cells might contribute to fibrotic progression through various mechanisms including microbial sensing pathways.…”
Section: Evidence For the Expansion Of Pericyte-derived Fibroblasts Amentioning
confidence: 99%
“…58 In addition, myofibroblast activation is also accompanied by innate immune system, partially through the secretion and expression of pro-inflammatory cytokines. 17,59 Among the pro-inflammatory cytokines and growth factors, IL-1β, IL-6, and TGF-β1 are the typical factors, released by leukocytes that traffic to the damaged kidney tissue. 60,61 These inflammatory cytokines induce the activation of fibroblasts, which are strong producers of the ECM component.…”
Section: Discussionmentioning
confidence: 99%